Application of Happy Mathematics Method to Increase Learning Motivation of Grade 2 Elementary School Students - Rizal Rizal; Muhajhidah Muhajhidah; Salmia Salmia (Edumaspul: Jurnal Pendidikan, 2025)
This study, titled "Application of the Joyful Math Method to Increase Motivation in 2nd Grade Students", aims to explore the impact of the Joyful Math method on enhancing students' motivation in learning mathematics at the elementary school level. The research focuses on implementing interactive and enjoyable activities, such as games and hands-on learning tools, to make mathematics more engaging for 2nd-grade students who often perceive it as difficult and boring. Data were collected through observations, interviews with teachers, students, and the school principal, as well as relevant documents. The results indicate that the Joyful Math method significantly improved students' enthusiasm and active participation in mathematics lessons, reducing anxiety and increasing confidence in solving math problems. However, challenges such as time constraints and limited learning materials were identified as obstacles in fully implementing the method. Despite these challenges, the study suggests that with proper support from the school and additional resources, the Joyful Math method holds great potential for fostering long-term motivation and improving mathematical achievement. This research contributes to the field by introducing a creative approach to elementary mathematics education, highlighting its effectiveness in boosting student motivation and engagement through enjoyable learning experiences.